Thymomas: five-year outcomes of open surgery and a single centre experience - Baram, Aram (J Int Med Res, 2019)
OBJECTIVE: To present and discuss the clinical course, management, recurrence and survival of patients with thymoma at a single centre. METHODS: This prospective observational study included patients with confirmed thymoma who were diagnosed and managed over a 10-year period. RESULTS: The study included 89 patients (mean ± SD age, 48.53 ± 11.60 years). There were 46 (51.7%) males and 43 (48.3%) females. The mean duration of follow-up was 60 months (range, 2 months to 8 years). Stage II was the most common stage (37 [41.6%]), followed by stage I with 30 (33.7%) patients, stage IIIA with 11 (12.4%) patients, stage IVA with six (6.7%) patients and stage IIIB with five (5.6%) patients. Overall (actuarial) 5-year survival was achieved by 84 of 89 patients (94.4%). Stage-specific survival was as follows: 100% in stage I (30 of 30 patients), 100% in stage II (37 of 37 patients), 54.5% in stage IIIA (six of 11 patients), 80.0% in stage IIIB (four of five patients) and 50.0% in stage IVA (three of six patients). CONCLUSION: Complete surgical resection is the main modality used for the definitive diagnosis, staging and surgical cure of thymoma.